Otoprotective effects of farnesene against oxidative damage induced by paclitaxel - DİNCER, Büşra; ATALAY, Fatma; TATAR, Arzu (Cukurova Medical Journal, 2022)
Purpose: This study explores the biochemical and functional effects of farnesene, which has potent free radical scavenging and antioxidant properties, on paclitaxel-induced ototoxicity. Materials and Methods: Eighteen male Wistar albino rats were allocated into three groups of six rats at random. No paclitaxel or farnesene was given to the control group throughout the research. Paclitaxel was given four times intraperitoneally at a dose of 5 mg/kg (1st, 7th, 14th & 21st days) in the paclitaxel group. In the Farnesene + Paclitaxel group, 5 mg/kg paclitaxel was given first, followed by 4 times 50 mg/kg farnesene intraperitoneally 30 minutes later (1st, 7th, 14th & 21st days). Otoacoustic emission measurement was taken on days 0 and 21 in all rats. After that, the animals were sacrificed, and their cochleas were extracted for biochemical testing. Results: Paclitaxel caused oxidative stress in the cochlea, which considerably elevated malondialdehyde levels and lowered glutathione levels in cochlear tissues. Furthermore, the paclitaxel group’s distortion product otoacoustic emission values were significantly lower than the other groups. Improvements in the damage produced by paclitaxel in various biochemical and functional parameters were observed in the Farnesene+Paclitaxel group. Conclusion: The study findings imply that farnesene, a natural antioxidant, reduced paclitaxel-induced hearing loss in rats, and a combination of farnesene and paclitaxel therapy may have protected from paclitaxel-induced ototoxicity for future clinical use.
Keywords: Antioksidanlar; Farnesen; Otoakustik emisyon; Ototoksisite; Paklitaksel; Klinik Tıp Bilimleri; Clinical Sciences; Antioxidants; Farnesene; Otoacoustic emission; Ototoxicity; Paclitaxel; Ototoxicity; 3. Good health